2020
DOI: 10.1039/d0ta01146k
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activation of a non-noble intermetallic surface through nanostructuration under hydrogenation conditions revealed by atomistic thermodynamics

Abstract: On the basis of DFT, we predict nanostructuration and subsequent catalytic activation of Al13Co4(100) under reaction conditions, while Al13Fe4(010) remains nanostructured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 61 publications
(54 reference statements)
2
11
0
Order By: Relevance
“…STM images were simulated using the Tersoff-Hamann approximation. 61 The approach used to compute surface energies in this work is the typical symmetric slab model, 62,63 already used in our previous studies, 35,64 wherein a supercell of the crystal oriented to expose its (hk ) surface is generated, and atoms are removed from a portion of the supercell to create a vacuum (16 to 24Å thick symmetric slabs, void thickness 16Å). This set-up for surface modeling leads to surface energies converged within less than 2.0 mJ/m 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…STM images were simulated using the Tersoff-Hamann approximation. 61 The approach used to compute surface energies in this work is the typical symmetric slab model, 62,63 already used in our previous studies, 35,64 wherein a supercell of the crystal oriented to expose its (hk ) surface is generated, and atoms are removed from a portion of the supercell to create a vacuum (16 to 24Å thick symmetric slabs, void thickness 16Å). This set-up for surface modeling leads to surface energies converged within less than 2.0 mJ/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…11). Two surface models are available for the pseudo-tenfold surface: a dense Alrich flat plane, identified by a combination of surface science studies and DFT calculations (P 24 ), [32][33][34] and a highly corrugated model, keeping intact the Henleytype clusters at the surface (P 14 ), 24,35,46 build by a model), they turn up to be the most stable in the full range of allowed chemical potentials, with surface energies ranging from 1.19 J/m 2 (Co-rich potentials) to 1.31 J/m 2 (Al-rich potentials). Thus, they substantially contribute to stabilize the pseudo-twofold orientation over the pseudo-tenfold one.…”
Section: Detailed Surface Model For the Pseudotwofold Surface Of O-almentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the monoclinic phases of Al13Co4 and Al13Fe4 possess similar crystallographic structures and may form a continuous solid-solution of Al13(Fe,Co)4 [28,48], which is not observed in the case of other transition metals. The experimental and theoretical studies revealed that the formation enthalpy of Al13Co4 is more negative than the Al13Fe4 phase [49]. This can be the reason for the lower formation enthalpy and a smaller volume of Al78(Fe23Co) phase than the Al78(Fe23M) phase (M = Cr, Mn On the other hand, the addition of Cr and Mn increased the formation enthalpy of the compound and decreased its stability.…”
Section: Formation Enthalpy Of Al 13 Fe 4 Phasementioning
confidence: 99%